2020
DOI: 10.1093/brain/awaa338
|View full text |Cite
|
Sign up to set email alerts
|

Local sleep-like cortical reactivity in the awake brain after focal injury

Abstract: The functional consequences of focal brain injury are thought to be contingent on neuronal alterations extending beyond the area of structural damage. This phenomenon, also known as diaschisis, has clinical and metabolic correlates but lacks a clear electrophysiological counterpart, except for the long-standing evidence of a relative EEG slowing over the injured hemisphere. Here, we aim at testing whether this EEG slowing is linked to the pathological intrusion of sleep-like cortical dynamics within an awake b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
79
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 55 publications
12
79
0
Order By: Relevance
“…However, this model does not recapitulate the graded ischemic injury observed in the penumbra of natural strokes. In the setting of a true ischemic penumbra, EEG studies in humans have demonstrated that SW sleep activity is increased around infarcts (57) in tandem with the emergence of pathological peri-infarct SWs during wakefulness (58). Thus, stroke may disrupt SWs by divergent mechanisms, both due to death of circuits generating SWs, as well as dysfunction in surviving neurons in the periinfarct zone.…”
Section: Discussionmentioning
confidence: 99%
“…However, this model does not recapitulate the graded ischemic injury observed in the penumbra of natural strokes. In the setting of a true ischemic penumbra, EEG studies in humans have demonstrated that SW sleep activity is increased around infarcts (57) in tandem with the emergence of pathological peri-infarct SWs during wakefulness (58). Thus, stroke may disrupt SWs by divergent mechanisms, both due to death of circuits generating SWs, as well as dysfunction in surviving neurons in the periinfarct zone.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings based on TMS, fMRI and EEG studies pointed out that cortico-subcortical and subcortical stroke patients have different cortical activity and excitability levels of the motor cortex ( Luft et al, 2004 ; Thickbroom et al, 2015 ; Lamola et al, 2016 ; Fanciullacci et al, 2017 ; Sarasso et al, 2020 ). However, the impact of these differences on functional outcome has not been fully elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Future approaches should seek relationships and convergence between metrics derived from information theory, graph theory, and dynamical systems theory and strive to connect them with structural measures. Contemporary examples include the recent link found between PCI and subcortical atrophy [ 76 ] and the recent association between focal cortical lesions and the generation of pathological slow waves, disconnection, and lost complexity [ 77 , 78 ].…”
Section: Results Of Gap Analysismentioning
confidence: 99%
“…This could be further enhanced through comparison with results from sleep and anesthesia research, in which microscopic mechanisms have been more comprehensively probed in preclinical work [ 87 ], producing mechanistic frameworks that span from whole-brain phenomena, such as individual susceptibility, to anesthetic-state transitions (neural inertia), all the way to genetic susceptibility factors for anesthesia [ 38 , 88 , 89 ]. Indeed, work in rodents and cortical slices alike has recently demonstrated that neuronal “off” periods determine a dramatic collapse of large-scale interactions and complexity during non-REM sleep and anesthesia [ 90 – 92 ], which can also be assessed by using EEG coupled with TMS in humans with brain damage [ 77 , 78 ].…”
Section: Linking Micro- and Macroscalesmentioning
confidence: 99%